Potensi Bakteri Endofit Pelarut Fosfat dan Penghasil IAA pada Pertumbuhan Tanaman Cabai - Zulfatma Amanda; Erman Munir; Isnaini Nurwahyuni (Jurnal Penelitian Pendidikan IPA, 2024)
Biofertilizer is considered an alternative to chemical fertilizers for enhancing plant productivity while minimizing ecological damage. Endophytic bacteria have the ability to solubilize phosphate and produce IAA (indole acetic acid). The aim of this research is to assess the phosphate solubilization and IAA production abilities of bacterial isolates applied to chili plants. Seven bacterial isolates collection from the Microbiology Laboratory, Universitas Sumatera Utara, were tested. In quantitative tests conducted in vitro, isolates MB10 and MB11 demonstrated the highest phosphate solubilization capabilities, yielding solubilization indices of 16.2 mm and 9.5 mm, respectively. Additionally, the ability of bacterial isolates to produce IAA in vitro was evaluated using calorimetry, revealing that isolates MB8 and MB2 produced the highest concentrations of IAA, measuring 58.58 ppm and 54.64 ppm, respectively. Furthermore, in vivo application involved the inoculation of isolates MB10 and MB11 on chili plants for 30 days. Seed treatment with suspensions of isolates MB10 and MB11 resulted in decreased plant performance compared to the control. These findings indicate that some endophytic bacteria originating from the mangrove root Avicennia marina have potential for producing relatively high levels of secondary metabolites. However, direct application did not significantly enhance plant growth performance.